Features of the microstructure of Ti–Nb alloy obtained via selective laser melting; Bulletin of the Russian Academy of Sciences: Physics; Vol. 81, iss. 11 - Sharkeev Yu. P. Yury Petrovich; Eroshenko A. Yu. Anna Yurjevna; Khimich M. A. Margarita Andreevna; Glukhov I. A. Ivan Aleksandrovich; Kovalevskaya Zh. G. Zhanna Gennadievna; Nikonova I. V. Irina Viktorovna (2018, 2018)
Title screen